Self-Financing Genocide : The Gold Train, the Becher Case and the Wealth of Hungarian Jews - Kádár, Gábor (Book collections on Project MUSE., 2004)
"Recounts the economic annihilation of the Hungarian Jews, who - from an economic point of view - were most influential than any other Jewish community in Europe. Following the German occupation in March 1944, the collaborating Hungarian government attempted to assert its claim concerning the complete confiscation of Jewish assets at all stages along the road leading to the extermination camps." "The book analyzes the role played by SS-Obersturmbannfuhrer Kurt Becher, one of the most controversial and mysterious figures in the Hungarian and universal history of the Holocaust. Becher, delegated to Hungary by Himmler, administered and benefited from the confiscation of an enormous amount of Jewish assets."--Jacket